PENGARUH KONTEN VIDEO VLOG PADA APLIKASI TIKTOK TERHADAP PEMBENTUKAN SIKAP MAHASISWA PERGURUAN TINGGI NEGERI (PTN) DI KOTA SAMARINDA - Tasya Lailatul Hakim; Kezia Arum Sary (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Vlogs are videos containing opinions, stories or daily activities that are usually written on blogs. Vlogs were initially a creative outlet for both Vloggers and their audiences. However, controversial trends have emerged that have the potential to be a bad influence on the audience, some Vloggers express themselves too freely and tend to be negative. To find out the Effect of Video Vlog Content on the TikTok Application on the Formation of Attitudes of State University Students (PTN) in Samarinda City. This research is quantitative, using a questionnaire to obtain data. The sampling technique used purposive sample and used the Slovin formula, which resulted in 100 people as respondents. The results of this study indicate that the video vlog content on the TikTok application has an influence of 51.6% on attitude formation, while the remaining 48.4% is influenced by other factors not included by the researcher. In the t-test results, the t-calculated value of 10.216 is greater than the t-table value of 1.984, which means that the Ha hypothesis is accepted that video vlog content affects attitude formation in state university students in Samarinda City.